Systemic pathological alterations caused by Philodryas patagoniensis colubrid snake venom in rats - Peichoto, María Elisa (2006)
Fil: Peichoto, María Elisa. Universidad Nacional Del Nordeste. Facultad de Ciencias Exactas, Naturales y Agrimensura; Argentina.